TOWARD LEXICAL BUNDLES IN GEORGIAN LEARNER CORPUS OF ENGLISH WITH IMPLICATIONS FOR PEDAGOGIC LEXICOGRAPHY - Makhatadze, Marine (Online Journal of Humanities ETAGTSU, 2024)
A primary component of fluent language production is the control of complex lexemes, known as lexical bundles, chunks, or clusters. These frequently recurring sequences of words (e.g., as compared to) function as building blocks of discourse, helping to shape meanings in specific contexts and contributing to our sense of coherence in a text. This paper is based on the corpus analysis with a combination of quantitative and qualitative criteria. To observe the idiosyncrasies and difficulties non-native writers face in producing accurate texts in English, the author compiled the Georgian Learner Corpus of English (GLEAN). Corpus data comprises argumentative essays, reports, narrative essays, and free composition essays within linguistics and literature, as well as blog posts, diaries and political/apolitical newspaper articles from Georgian learners of English. The aims of this research are as follows: a) to identify which lexical bundles (or lexical phrases) are most common in academic prose produced by Georgian learners of English; b) to classify the functions of the most common 3-word or 4-word lexical bundles used in the GLEAN corpus; and c) to highlight the value of adding the learner corpus data (such as illustrative sentences, usage notes, “help boxes”) to learner dictionaries. The research results showed that the most frequent bundles in the Georgian Learner English corpus serve the primary function of participant-oriented bundles, which express attitudes. The final product is a list of 42 lexical bundles that cover academic writing in the GLEAN corpus disciplines (literature, linguistics, press, blog posts, etc.) and the lexicographic implications for further research. Full Text (PDF)